2020
DOI: 10.5114/aoms.2020.98350
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in heart failure patients undergoing hybrid comprehensive telerehabilitation versus usual care – results of the Telerehabilitation in Heart Failure Patients (TELEREH-HF) Randomized Clinical Trial

Abstract: Introduction: Hybrid comprehensive telerehabilitation (HCTR) consisting of telecare (with psychological telesupport), telerehabilitation and remote monitoring of implantable devices might be an innovative option improving heart failure (HF) patients' quality of life (QoL) and emotional health. The aim of the study was to investigate the influence of HCTR on various facets of QoL in HF patients in comparison with usual care (UC) alone. Material and methods: The present analysis formed part of a multicenter, ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…This analysis focuses on patients randomized to the HCTR group. A total of 27 patients did not participate in HCTR program due to: technical difficulties with operating the telerehabilitation set (21), new onset of comorbidities (4), return to work (2) [17]. Finally, 398 patients started HCTR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis focuses on patients randomized to the HCTR group. A total of 27 patients did not participate in HCTR program due to: technical difficulties with operating the telerehabilitation set (21), new onset of comorbidities (4), return to work (2) [17]. Finally, 398 patients started HCTR.…”
Section: Resultsmentioning
confidence: 99%
“…It concerns patients' understanding of the necessity to follow both regular exercise training and daily pharmacological treatment as well as appropriate diet and promotion of mental health. The main analysis of the entire population of TELEREH-HF RCT demonstrated that a 9-week HCTR significantly improves the physical capacity and quality of life of HF patients in contrast with the usual care [17,21]. Yet, it had no significant impact on mortality and rehospitalization rates in a long-term follow-up [17].…”
Section: Discussionmentioning
confidence: 99%
“…The question is why in our study the functional improvement after telerehabilitation did not affect the occurrence of nsVT or PVCs ≥ 10. Perhaps the period of 9 weeks of telerehabilitation is sufficient to improve physical capacity but too short to trigger the beneficial effect of long-term moderate exercise on preventing arrhythmias, particularly the improvement in autonomic balance in favor of the vagal component and the improvement in baroreflex sensitivity [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…13,14 These considerations underscore the importance of exercise training plan in terms of its type (endurance, resistance and strength), intensity (aerobic versus anaerobic); method (continuous versus intermittent/interval); setting (centre-based versus home-based); application (systemic, regional and respiratory muscle) and control (supervised versus non-supervised). 15 This highly systematic approach to training makes it safe as therapeutic strategy in HF patients.…”
Section: Heart Failure Va and The Safety Of Exercise Trainingmentioning
confidence: 99%
“…This association may be due to a decrease in the left ventricular volume overload [ 26 ]. Furthermore, cardiac rehabilitation may be associated with improvement in exercise tolerance in patients with HF (reduction in NYHA class, improvement in peak oxygen consumption and an increase in the distance during the six-minute walk test) and improvement in three specific areas of quality of life: physical functioning, role functioning related to physical state and bodily pain [ 17 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%